Achieving Mastery of General Surgery Operative Skill in the Army Healthcare System. Issue 3 (12th September 2018) - Plackett, Timothy P; Brockmeyer, Joel R; Holt, Danielle B; Rush, Robert M; Sarkar, Joy; Satterly, Steven A; Seery, Jason M; Zagol, Bradley R
Abstract: Introduction: Operative case volumes for military surgeons are reported to be significantly lower than civilian counterparts. Among the concern that this raises is an inability of military surgeons to achieve mastery of their craft. Material and Methods: Annual surgical case reports were obtained from seven Army military treatment facilities (MTF) for 2012–2016. Operative case volume and cumulative operative time were calculated for active duty general surgeons and for individual MTFs. Subgroup analyses were also performed based upon rank. Results were extrapolated to calculate the amount of time it would take to reach a cumulative of 10, 000 hours of operative time (the a priori definition for achieving mastery). Results: One hundred and two active duty general surgeons operated at the seven MTFs during the study period and met the inclusion criteria. The average surgeon performed 108 ± 68 cases/year. The average surgeon operated 122 ± 82 hours/year. At this rate, it would take over 80 years to reach mastery of surgery. When stratified based upon rank, Majors averaged 113 ± 75 hours/year, Lieutenant Colonels averaged 170 ± 100 hours/year, and Colonels averaged 136 ± 101 hours/year ( p < 0.05). When stratified based upon individual MTF, surgeons at the busiest facility averaged 187 ± 103 hours/year and those at the least busy facility averaged 85 ± 56 hours/year ( p < 0.05). Conclusions: Obtaining mastery of general surgery is a nearly impossible proposition given the current care models at Army MTFs. Alternative staffing and patient care models should be developed if Army surgeons are to be masters at their craft.